Pengaruh Kualitas Produk dan Kepuasan Konsumen Halsean Coffee & Resto di Kota Cimahi, Indonesia - Aulia Alfita Hannan (International Journal Administration, Business & Organization, 2022)
In this era of globalization, business actors are required to be more creative and innovative in creating their businesses in order to compete with new competitors. One of the businesses that is in great demand and the current trend is in the retail sector, especially in the coffee shop sector in Greater Bandung. In building a coffee shop, it is necessary to pay attention to good product quality, because this is one of the factors that influence consumer satisfaction. Therefore, this study was made with the aim of examining the effect of product quality on consumer satisfaction at Halsean Coffee & Resto in Cimahi City. This study uses a descriptive method with a quantitative approach. A total of 101 visitors to Halsean Coffee & Resto in the Cimahi and surrounding areas were involved in this research. Data analysis in this study used descriptive analysis, factor analysis, and simple regression analysis with the help of SPSS v.23 software. The results of data analysis showed that product quality has a positive and significant direction on consumer satisfaction.